Impact of Sarcopenia on Outcomes Following Resection of Pancreatic Adenocarcinoma - Peng, Peter (2012)
INTRODUCTION: Assessing patient-specific risk factors for long-term mortality following resection of pancreatic adenocarcinoma can be difficult. Sarcopenia—the measurement of muscle wasting—may be a more objective and comprehensive patient-specific factor associated with long-term survival. METHODS: Total psoas area (TPA) was measured on preoperative cross-sectional imaging in 557 patients undergoing resection of pancreatic adenocarcinoma between 1996 and 2010. Sarcopenia was defined as the presence of a TPA in the lowest sex-specific quartile. The impact of sarcopenia on 90-day, 1-year, and 3-year mortality was assessed relative to other clinicopathological factors. RESULTS: Mean patient age was 65.7 years and 53.1 % was male. Mean TPA among men (611 mm(2)/m(2)) was greater than among women (454 mm(2)/m(2)). Surgery involved pancreaticoduodenectomy (86.0 %) or distal pancreatectomy (14.0 %). Mean tumor size was 3.4 cm; 49.9 % and 88.5 % of patients had vascular and perineural invasion, respectively. Margin status was R0 (59.0 %) and 77.7 % patients had lymph node metastasis. Overall 90-day mortality was 3.1 % and overall 1- and 3-year survival was 67.9 % and 35.7 %, respectively. Sarcopenia was associated with increased risk of 3-year mortality (HR=1.68; P<0.001). Tumor-specific factors such as poor differentiation on histology (HR=1.75), margin status (HR=1.66), and lymph node metastasis (HR=2.06) were associated with risk of death at 3-years (all P<0.001). After controlling for these factors, sarcopenia remained independently associated with an increased risk of death at 3 years (HR=1.63; P<0.001). CONCLUSIONS: Sarcopenia was a predictor of survival following pancreatic surgery, with sarcopenic patients having a 63 % increased risk of death at 3 years. Sarcopenia was an objective measure of patient frailty that was strongly associated with long-term outcome independent of tumor-specific factors.